IRON DEFICIENCY ANEMIA AND ITS RELATIONSHIP WITH SOCIOECONOMIC VULNERABILITY - Élida Mara Braga Rocha; Amanda Forster Lopes; Silvia Maira Pereira; Claudio Leone; Luiz Carlos de Abreu; Patricia Dore Vieira; Sophia Cornbluth Szarfarc
ABSTRACT Objective: To analyze the association of anemia with the socioeconomic vulnerability of preschoolers in public day care centers, in the city of Taubaté, SP, Brazil. Methods: This is a cross-sectional study with a probabilistic sample that analyzed 363 children assisted in public day care centres in low-income and high-income areas of Taubaté, SP, Brazil. The hemoglobin concentration (Hb), dependent variable, was obtained by digital puncture, considering anemic children with Hb concentration <11.0 g/dL. The independent variables such as socioeconomic and demographic conditions were collected by a semi-structured questionnaire. Results: The prevalence of iron deficiency anemia was 19.3% among preschoolers. Children from day care centers with high socioeconomic vulnerability had lower Hb concentration than those from a non-vulnerable area (p<0.05). Conclusions: The lower concentration of hemoglobin in preschoolers is associated with the location of day care centers in an area of socioeconomic vulnerability. Children attending these day care centers face adverse family conditions such as low income, working mothers, and mothers with low schooling, though they receive social benefits and monitoring by public health services.